THE EFFECT OF SERVICE QUALITY AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY GAPOKTAN MAJU CIMANGGIS DEPOK - Mudatsir Najamuddin; Puspi Eko Wiranthi; Arin Annisa (Syarif Hidayatullah State Islamic University Jakarta, 2021)
PT. Gapoktan Maju Bersama is one of the farmer institutions engaged in the collection and marketing of star fruit with the god variety. Gapoktan Maju Bersama has been established in 2011 where gapoktan customers are Indomaret, Indogrosir, UD Perdana Juice, and PT Delira Sejahtera. However, the existence of competitors who are fellow star fruit suppliers who threaten the existence of Gapoktan Maju Bersama, makes customers much more entrusted with the supply of star fruit to competitors. Indications of dissatisfaction are in the form of dissatisfied customers with the quality of service. Data collection in this study used the method of interviewing with questionnaires, observations, and literature studies. The questionnaire given is related to questions about service quality, customer satisfaction, and customer loyalty. The answer measurement technique in this study used Likert scale measurements with a scale range of 1 to 4. Sampling in this study was nonprobability sampling with a purposive sampling method. These respondents are business owners, receiving, purchasing, buyers, and store managers. The exogenous variables of this study are service quality and customer satisfaction. The endogenous variable is Customer Loyalty. The research was conducted using the Structural Equation Modelling method with a Partial Least Square approach. The research was processed with Ms. Excel 2016, IBM SPSS, and SmartPLS 3.0. The results of this study show an influence between service quality on customer loyalty, customer satisfaction on customer loyalty, service quality on customer satisfaction, and the influence of service quality on customer loyalty through customer satisfaction. The sub-variables that have successive effects are physical evidence, empathy, assurance, reliability, and responsiveness. Then from customer satisfaction, the most influential successively is the willingness to recommend, the interest in visiting again, and the conformity to expectations.